Analisis Dampak Luapan Sungai Citarum Terhadap Stabilitas Bendungan Saguling - Febri Attala Deka; Rifansyah Rifansyah; Dani Lukman Nurhakim; Arya Putra Pratama; Luthfi Akbar; Ziyyan Nugraha (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The overflow of the Citarum River is one of the main challenges in maintaining the stability of the Saguling Dam in Indonesia. This research aims to analyze the impact of the Citarum River overflow on the stability of the dam. The methods used include field surveys, hydrological data analysis, and numerical modeling. This research makes an important contribution to understanding the interaction between river overflows and dam stability, and provides a basis for developing disaster risk mitigation strategies in areas vulnerable to floods and river overflows.